A Systematic Literature Review of Online Peer Feedback: Uncovering the Current Situation in EFL Setting - Hidayatulloh, Sibakhul Milad Malik (SALEE: Study of Applied Linguistics and English Education, 2025)
This paper digs into the landscape of online peer feedback in English as a Foreign Language (EFL) context which aims to provide a comprehensive overview of its practices and implementation strategies. Having literature review as the source of finding the current practices, 59 articles were chosen as the basis of the current study justification in mapping the current practices in online peer feedback. The findings reveal that over the past decade, the practices of online peer feedback in EFL have become increasingly diverse, extending beyond specific educational levels. As time progresses, advancements in response strategies, ICT-supported tools, and practical methodologies have enriched these practices.  By presenting a detailed account of the current state of online peer feedback in EFL settings, this paper seeks to support teachers and practitioners in navigating and implementing effective strategies. It aims to serve as a guide for understanding and selecting appropriate methods to integrate online peer feedback into classroom settings, ultimately enhancing learning outcomes.